A New Vision for Enhancing Women’s Leadership Role in Higher Education Decision-Making - Tlepina, Sholpan; Sarsembayev, Marat; Abaideldinov, Yerbol; Balmagambetova, Venera; Zhunusbekova, Aigerim (Ital Publication, 2024)
Legal issues of gender equality and the principle of inadmissibility of discrimination against women in all spheres of life are becoming relevant worldwide, including in the Republic of Kazakhstan. This study aims to show ways to enhance the role of women in the higher education system, which is necessary to implement the principle of real equality in relationships with men, the principle of fair distribution of managerial positions without gender discrimination, and the implementation of leadership activities by women due to their managerial potential. To achieve this goal, the authors have researched this topic in a comparative legal format, comparing the practice and legal peculiarities of Kazakhstan and some developed countries. We used logical analysis, comparative legislative analysis, legal analysis, and legal forecasting. Kazakh legislative acts that promote the expansion of women’s rights while enhancing the role of women in higher education were analyzed. The practical results of the study consist in the formulation and justification of organizational and legal ways to increase the leadership role of women in higher education in the Republic. The scientific novelty lies in the previously unexplored topic of gender equality in the higher education system of Kazakhstan from a legal viewpoint. The conclusion about gender asymmetry should encourage other researchers to study this problem on a larger scale and deepen the understanding that only clearly, competently, and equally selected leaders of both sexes can positively influence the accelerated development of the higher education system and ensure the actual competitiveness of Kazakhstani universities and their graduates. Doi: 10.28991/ESJ-2024-08-05-016 Full Text: PDF